Retropubic versus transobturator tension‐free vaginal tape (TVT vs TVT‐O): Five‐year results of the Austrian randomized trial. Issue 1 (2nd May 2017) - Tammaa, Ayman; Aigmüller, Thomas; Hanzal, Engelbert; Umek, Wolfgang; Kropshofer, Stephan; Lang, Peter F. J.; Ralph, George; Riss, Paul; Koelle, Dieter; Jundt, Katharina; Tamussino, Karl; Bjelic‐Radisic, Vesna; et al.
Abstract : Aims: To compare outcomes of the retropubic versus the transobturator tension‐free vaginal tape (TVT vs TVT‐O) at 5 years. Methods: A total of 569 women undergoing surgery for primary stress incontinence were randomized to receive a retropubic or a transobturator tensionfree vaginal tape (TVT or TVT‐O). Follow‐up at 5 years included clinical examination, urodynamic studies and quality of life. The primary outcome measure was continence defined as a negative cough stress test at a volume of 300 mL. Secondary outcomes included urodynamic parameters, complications and quality of life.ClinicalTrials.gov (NCT 0041454). Results: Three hundred and thirty‐one patients (59%) were evaluated at 5 years (277 were seen, examined and completed questionnaires; 54 only completed questionnaires). No significant differences were seen in rates of a negative cough stress test (83% vs 76%, respectively), urodynamic parameters and complications. Quality‐of‐life improved significantly in both groups, without significant differences between the groups. Erosion rates were 5.2% and 4.5%, and reoperation rates were 4.1% and 3.2% respectively. Conclusions: At 5 years, subjective and objective results after TVT and TVT‐O are stable and similar, without statistical significant differences between the procedures. Major long‐term problems appear rare.